Exploring religion based persuasive factors to rationalise violence among Muslim youth in Malaysia - Yusof, Norhafezah; Awang Hashim, Rosna; Mohd Sani, Mohd Azizuddin; Dalib, Syarizan; Ramli, Romlah
The current study presents a qualitative experimental design that combines the elements of an experiment with qualitative design to investigate the persuasive factors that rationalize violence among youth in Malaysia. Data was collected using semi-structured interviews from twenty-four participants who were exposed to an intervention of videos and PowerPoint slides to elicit their responses on a situation. This study provides a way to understand factors that could lead selected youths to rationalize extremism in a society. The findings provide insight into the role of persuasive messaging in recruiting youth towards extremist behaviours.